Cultural Loss and Mediation in Translating Javanese Material Culture: A Case Study of Para Priyayi and Ein Hauch von Macht: Penelitian - Nila Viayanti Mala; Diyan Fatimatuz Zahro (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study investigates the translation of material culture elements in Para Priyayi, a novel by Umar Kayam, into German in its translated version Ein Hauch von Macht, focusing on cultural loss and mediation strategies. Using a qualitative descriptive method, the study analyzes 146 instances of material culture identified in the corpus and classifies them based on translation techniques. The results show that 63 entries exhibit cultural loss, mainly through borrowing, particularization, generalization, omission, and reduction. Meanwhile, 41 entries involve mediation strategies such as adaptation, description, amplification, modulation, and substitution. The remaining 42 entries are neutral, employing literal translation, established equivalent, and transposition. Cultural loss occurs when no direct equivalents exist in the target culture or when contextual information is insufficient, whereas mediation strategies help target readers understand complex cultural meanings. The findings highlight the translator’s role as a cultural mediator, underscoring the importance of cultural sensitivity and contextual awareness in literary translation.